OPTN/SRTR 2011 Annual Data Report: Heart. (13th December 2012) - Colvin‐Adams, M.; Smith, J. M.; Heubner, B. M.; Skeans, M. A.; Edwards, L. B.; Waller, C.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
Abstract : ABSTRACT  Since 2005, the number of new active adult candidates on the heart transplant waiting list increased by 19.2%. The transplant rate peaked at 78.6 per 100 wait‐list years in 2007, and declined to 67.8 in 2011. Wait‐list mortality declined over the past decade, including among patients with a ventricular assist device at listing; in 2010 and 2011, the mortality rate for these patients was comparable to the rate for patients without a device. Median time to transplant was lowest for candidates listed in 2006–2007, and increased by 3.8 months for patients listed in 2010–2011. Graft survival has gradually improved over the past two decades, though acute rejection is common. Hospitalizations are frequent and increase in frequency over the life of the graft. In 2011, the rate of pediatric heart transplants was 124.6 per 100 patient‐years on the waiting list; the highest rate was for patients aged less than 1 year. The pre‐transplant mortality rate was also highest for patients aged less than 1 year. Short‐ and long‐term graft survival has continued to improve. The effect on wait‐list outcomes of a new pediatric heart allocation policy implemented in 2009 to reduce pediatric deaths on the waiting list cannot yet be determined.